Quality of language exams in evaluation of professional communicative competence - Gordiyenko, O.; Myroshnychenko, O.; Dmyterko, Ye.; Мирошниченко, Олена Анатоліївна; Гордієнко, Олена В'ячеславівна (My University, 2022)
The article is devoted to the quality of some popular language exams to assess the level of professional Englishlanguage communicative competence. The paper analyzes the structure of popular international exams in English and English for specific purposes. Requirements for the level of English proficiency of medical students in accordance with CEFR have been determined. The article highlights the purpose and objectives of the exams KROK-1 (ESP), CAE, TOLES, BEC, APTIS, OET in terms of their structure. The standards of international English language exams have been considered and groups of exams that are mandatory for admission to universities, for work abroad and for assessing the level of English for professional purposes in medicine are identified. The structure and content of the exams have been revealed. The quality of the qualification exam KROK-1(ESP) in comparison with the existing CAE, TOLES, BEC, APTIS, OET on checking the level of professional communicative competence of medical students has been analyzed. The purpose of exams that reveal the level of English language proficiency at the professional level was considered. The structure of each exam was analyzed, namely the mandatory parts of the exam that must be passed and the duration of the tasks, their types. Certain skills that are tested during the exam have been identified. This article also considered the quality parameters of the qualification exam KROK-1(ESP) in accordance with the requirements of the level of English language proficiency according to the CEFR. The obtained results were compared, and conclusions were drawn on the validity of the tests for comprehensive assessment of the level of professional English-language communicative competence. Статтю присвячено питанням якості іспитів щодо оцінювання рівня професійної англомовної комунікативної компетенції. У роботі проаналізовано структуру популярних міжнародних іспитів з англійської мови та з англійської мови професійного спрямування. Визначено вимоги до рівня володіння англійською мовою професійного спрямування у студентів медиків відповідно до CEFR. У статті виокремлено мету та завдання іспитів КРОК-1 (АМПС), CAE, TOLES, BEC, APTIS, OET у розрізі їхньої структури. Розглянуто стандарти міжнародних іспитів з англійської мови та виявлено групи іспитів, які є обов’язковими для вступу до вишів, для отримання роботи за кордоном та загалом є кваліфікаційними іспитами для оцінювання рівня англійської мови професійного спрямування у галузі медицини. Розкрито структуру та наповнюваність іспитів професійного спрямування та загальних іспитів. Проаналізовано якість кваліфікаційного іспиту КРОК- 1(АМПС) у порівнянні з існуючими CAE, TOLES, BEC, APTIS, OET щодо перевірки рівня професійної комунікативної компетенції студентів медиків. Розглянуто мету іспитів, які виявляють рівень володіння англійською мовою на професійному рівні. Проаналізовано структура кожного іспиту, а саме обов’язкові частини іспиту, які необхідно скласти та тривалість виконання завдань, їх типи. Виявлено певні навички, які перевіряються під час іспиту. У статті також було проаналізовано параметри якості кваліфікаційного іспиту КРОК-1(АМПС) відповідно до вимог рівня володіння англійською мовою згідно до CEFR. Отримані результати було зіставлено та зроблено висновки щодо валідності тестів для комплексного оцінювання рівня професійної англомовної комунікативної компетенції.
Якість мовних іспитів у оцінюванні професійної комунікативної компетенції
Keywords: structure of international language exams; level of English language proficiency; Language for specific purposes; Cambridge Exams; TOLES; BEC; APTIS; OET; KROK-1(ESP); структура міжнародних мовних іспитів; рівень володіння англійською мовою; мова для спеціальних цілей; Cambridge Exams; КРОК-1 (АМПС)